Mapping changes in the utilization of childhood immunization over 5 years in a south Indian tertiary care hospital - Merrin Mathew; Savitha Rajapur Sanathan; Juny Sebastian; Mandyam Dhati Ravi; Taniya Joy; Rovin Mathew Theempalangad; Panchaksharappa Gowda (SAGE Publishing, 2024)
Background: Altered vaccine demands and uneven utilization patterns in childhood immunization are evident nationwide. These variabilities may stem from a range of internal and external factors influencing parental preferences. Regular checks and balances are necessary to ensure equal accessibility for all sections of society. Aim: To assess the usage trends of childhood vaccines for 5 years (2018-2022) and to monitor instances of delayed/incomplete immunization status within the community. Methodology: This study recorded the utilization trends of all recommended childhood vaccines over a 5-year period using an ambispective design. The immunization details from 3 years (2018, 2019 and 2020) were retrieved retrospectively, while those from 2 years (2021-2022) were collected prospectively through the immunization registry. Trends in childhood vaccine utilization were recorded across different years, and delays and incomplete vaccine utilization among children, along with factors resulting in deviated immunization timelines, were analysed and compared. The association of factors with deviated immunization utilization was determined using the chi-square test, and a two-way ANOVA analysed utilization variabilities over 5 years. Result: Overall, the study profiled 32,085 children's (who utilized 87,782 vaccine doses) vaccine utilization pattern for 5 years. Optional vaccines were less utilized (18.12% doses by 25.14% children) compared to mandatory vaccines (81.88% doses utilized by 74.86%). The most utilized mandatory vaccine was oral polio (17.48%) and for optional vaccines, it was measles mumps rubella (MMR; 28.31%). Boys had the highest utilization (55.97%) with a significant male preponderance in optional vaccine utilization ( p value <0.05). Overall, there was a 26.12% decline (percent change) in vaccine utilization in 2022 compared to 2018. Among children with delayed immunization timelines (6.02%), 3.38% were on catch-up, and 2.45% were not. The most commonly delayed vaccines were diphtheria + tetanus + pertussis boosters (30.90%), Tdap (26.19%) and MMR vaccines (20.65%). Influenza vaccines (28.08%) were the most partially utilized optional vaccine, followed by varicella vaccines (20.92%). Factors such as gender (female), age over 1 year, rural residence and low- to middle-income families were significant predictors of deviated immunization status in children. Conclusion: The study mapped the utilization trends of immunizations at a tertiary care hospital in south India over the past 5 years, including the COVID-19 years. Gender inequality in the utilization of optional vaccines is a concern that warrants further research and redressal. Timely administration of childhood vaccinations is crucial for reducing susceptibility to vaccine-preventable diseases and promoting overall well-being.